Giro lamo Savonarola and forms of government. - Salatini, Rafael [UNESP] (Unesp-marilia, 2015)
The work presents an analytical study of the theme of the forms of government in the political thought of Girolamo Savonarola, based on his Thatawo circa il regimento e governo dela cimi. di Firenze (1498). Using Bobbio's methodology, the theme is analyzed from three simultaneous perspectives: the systematical, the axiological, and the teleological.

O trabalho apresenta um estudo analítico do tema das formas de governo, no pensamento político de Girolamo Savonarola, a partir de Tratatto circa il regimento e governo dela città di Firenze (1498). Parte-se da metodologia bobbiana, analisando-se o tema sob três perspectivas simultâneas: sistemática, axiológica e teleológica.
Keywords: Savonarola; Forms of government; Civic humanism